Enhancing Water Quality Surveillance: A Comparative Analysis of Portable Microbiological Laboratory and the Colilert Quanti - Tray 2000, in North Nyakach Ward, Kisumu County - Ng’etich, Nancy Chebichii (JOOUST, 2023)
Operational water quality surveillance dominates urban piped systems. Lack of it poses a serious risk to public health as the population is exposed to disease-causing microorganisms; responsible for between four and six million cases of diarrhoea and more than 1,300 fatalities each day. Thus the need to determine the accuracy and reliability of the Portable Microbiology Lab (PML) for point sources of water, both protected and unprotected. The study evaluated the field test method, PML Kit under different water source conditions by comparing it to a laboratory standard method Quanti-Tray. This was executed by analyzing 27 water samples. PML and Quanti-Tray 2000 yielded matching risk-level results for 26 samples. For qualitative test of the 10mL and 100mL Colilert; 4 of the 27 samples' presence/absence tests were not congruent with each other. Thus error for a test with 10mL Colilert of PML resulted in a percentage variation of 14.81%, sensitivity of 82.6% and a specificity of 100%. The addition of Petrifilm to identify risk levels the proportional reduction in error relative to water source designation, for improved water source; for moderate levels 30.78%, low risk 30.78%, high/very high risk was at 7.69% with a statistically significant differenceχ 2 (2, n =13) = 30.78, d.f. =2, (p <0.0001). The Portable Microbiology Laboratory offers accurate and reliable water quality assessment in line with the WHO disease-risk levels and serve as a basis for informed management and public health interventions. This will facilitate consistent and widespread monitoring of water quality, ultimately leading to improved public health outcomes.
Keywords: Water; Water Quality; Water Quality Surveillance; Colilert Quanti - Tray 2000; Portable Microbiological Laboratory